Transcriptome analysis of high- and low-selenium genotypes identifies genes responsible for selenium absorption, translocation, and accumulation - Li, Ling; Ahsan, Muhammad Zahir; Li, Zhe; Panhwar, Faiz Hussain; Zhang, Yue; Luo, Dan; Su, Yang; Jia, Xiaomei; Ye, Xiaoying; Shen, Caihong; Wang, Songtao; Zhu, Jianqing (Frontiers in Plant Science, 2024)
Selenium is an essential micronutrient the human body requires, closely linked to health. Rice, a primary staple food globally, is a major source of human selenium intake. To develop selenium-enriched rice varieties, it is imperative to understand the mechanisms behind selenium's absorption and transport within rice, alongside identifying the key genes involved in selenium uptake, transport, and transformation within the plant. This study conducted transcriptome sequencing on four types of rice materials (two low selenium and two with high selenium contents) across roots, stems, leaves, and panicles to analyze the gene expression differences. Differential gene expression was observed in the various tissues, identifying 5,815, 6,169, 7,609, and 10,223 distinct genes in roots, stems, leaves, and panicles, respectively. To pinpoint the key delve into these differentially expressed genes and to identify the core genes linked to selenium contents, Weighted Gene Co-expression Network Analysis (WGCNA) was performed and ultimately, 10, 8, 7, and 6 core genes in roots, stems, leaves, and panicles respectively were identified. The identification of these core genes substantially aids in advancing our understanding of the molecular mechanisms involved in selenium absorption and transport during the growth of rice.